Perkuatan Oprit Jembatan Kali Jubang Jalan Tol Pejangan - Brebes Timur menggunakan Geotekstil - Fitri, Siti Nurlita (BENTANG : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
The Kali Jubang Bridge, located on the Pejagan Toll Road, West Brebes, Indonesia, has oprit-embankment elevation of 7m. The soil structure in the area around Kali Jubang is the soft-brownish clay. Soft clay has a low bearing capacity and high compressibility. Therefore, these issues caused the occurrence of landslides, broken bridge plates, and different surface level which causes bumpy pavement and danger to road users. Hence, it is necessary to reinforce the oprit of the Kali Jubang. The design of geotexstile was conducted to improve the bearing capacity by using a geotextile with tensile strength (Tult) of 150 kN/m2. Results found that the initial embankment (Hinitial) was 8.9 m to anticipate the 1.9 m consolidation decrease . The geotextile was designed with 35 layers using a layer thickness of 0.25m, a top fold length of 1m, and an appropriate length for the width of the embankment for each layer.